(untitled) (Marketing Journal, 2025)
This article analyzes the importance of competitiveness in the activities of insurance companies and its impact on the quality of insurance services and pricing. In addition, the influence of competitiveness on the strategies developed by insurance compani es is examined, and indicators for assessing the level of competitiveness are proposed.